EXPERIMENTS ON BIOMASS TRANSPORT INSIDE UPFLOW SLUDGE BLANKET REACTORS INTERMITTENTLY FED (Journal of Engineering, 2006)
This work describes the experimental activities developed to study the biomass transportphenomena occurring in upflow anaerobic reactor influencing the biomass washout. Theexperimental investigations have been carried outon pilot UASB fed with the aim to determine theheight to which washout is affected by: daily flow distribution; upflow velocity; concentration andsedimentation properties of the biomass. The experiments had shown a considerable influence onthe biomass behavior of the time interval between two successive feeds of the reactor. It was foundthat, if this period is more than 1 hr larger losses of the biomass into the effluent were obtained,independent of the upflow velocity. Shorter time periods give rise to a regular sludge expansion ofthe interface even with very high upflow velocities (up to 4 m/hr), and accordingly exhibit limitedsludge washout.